The Influence of Organizational Culture, Work Attitudes, Work Behavior and Work Conflict On The Employee's Performance of PT. Hastari - Letitia, Dita Amanda; Krisnandi, Herry; Digdowiseiso, Kumba (Ridwan Institute, 2024)
The purpose of this study is to understand the Influence of Organizational Culture, Work Attitudes, Work Behavior, and Work Conflicts on the Performance of PT. HASTARI in South Jakarta. The survey population used primary data by distributing the survey to 100 respondents. Analysis of this data uses inference and descriptive analysis. The survey in this study used primary data obtained from the distribution of questionnaires and processed in SPSS 25. From the results of the study, it is known that variables of organizational culture, work attitudes, work behavior, and work conflicts have a positive and significant impact on employee performance are classified as very strong. Dependent variables, or changes in employee performance, are understandably independent variables, a combination of organizational culture, work attitudes, work behavior, and work conflicts. This can be predicted by the ups and downs of employee performance.